Human Rights on the Internet under quarantine (on the example of E-Commerce): problematic aspects - Kivalov, Serhii (DIXI, 2022)
As a result of the introduction of quarantine measures on the territory of Ukraine and abroad, almost all spheres of social life underwent particular changes. This led to certain restrictions on human rights, as a result of which legal science faced the task of finalizing and adapting legal regulation in the field of protection of subjective rights on the Internet to the realities caused by the coronavirus crisis. The purpose of the study is to characterize the legal regulation regarding restrictions and protection of consumer rights on the Internet in quarantine conditions. The object of the study is public relations in the spheres of electronic commerce, protection of consumer rights, and human rights on the Internet in general. The subject of the study is social relations that arise during the protection of civil rights on the Internet under quarantine conditions. The research methods were general scientific and special scientific methods such as dialectical, systemic, structural, historical-legal, comparative-legal, formal-legal; methods of induction, deduction, analysis, and synthesis. As a result of the research work, a multi-disciplinary review of publications on the subject of study and the conclusions of scholars was carried out; a description of the theoretical and legal framework for regulating the protection of civil rights on the Internet in quarantine conditions is provided; examples of judicial practice are given; issues related to the taxation of activities in the field of Internet trade were analyzed; specific solutions for improving legal regulation are proposed.
Keywords: e-commerce; Internet trade; protection of consumer rights; quarantine; coronavirus